A Modification of Box-Cox Transformation - Wan Muhamad Amir Bin W Ahmad; Nyi Nyi Naing; Mohd Tengku Ariff Raja Hussein (Program Studi Statistika Unisba, 2007)
Data screening is the most important technique to check the nature of the data. One of the methodsto screen the data is the transformation method. There are a lot of transformations but the famousone is the Box-Cox Transformation. The purpose of this study is to find the alternative way oftransformation by making some modification of the original Box-Cox formula. As we know, the Box-Cox transformation method only transform the data if and only if the data in a positive values. If thevalues in the analysis are negative, the formula of the Box-Cox cannot be used. This problem alwaysoccur when the researcher want to transform the data which the values is negative. In thismethodology section, we will build an alternative method to solve the problem if the data in the studyare negative.